The Role of Self Regulation in Moderating The Environmental Influences to The Learning Outcome - Hermanto, Dwi; Wahyudin, Agus; Masrukan, Masrukan (Journal of Primary Education, 2018)
The purpose of the research is to describe the role of self regulation as the environmental influence moderation towards the learning outcome in the Integrated Islamic Primary School of Mayong in Jepara.This research used correlational method with ex post facto design. The data was collected through documentation and questionnaires, while the data analysis applied descriptive analysis and absolute difference value. The results of the research showed that self regulationwas able tosignificantly moderate the environmental influences toward the learning outcome. There are three main environment to be concern in this study. They are family, school, and society environment.The optimum environments moderated were family and school environments. However, the society environment did not show significant influence towards learning outcome because the aspects did not recognize the students’ existence as the society members. This research resultwas supported by the behavioral theory explaining that learning is a behavioral change which occurs through the stimulation (by environment) while response as the learning outcome. The results were also supported by social cognitive theory which emphasizes that the environment faced by individual is not randomly chosen, it is often chosen and changed by the individual usinghis behavior.